Aktivitas Afrodisiak in Vivo Ekstrak Etanol 70% Akar Lelak (Uvaria rufa Blume.) Pada Mencit (Mus musculus) Jantan - Taek, Maximus M.; Muslikh, Faisal Akhmal; Maulina, Novia; Sawjana, Oashiva H.; Azzahra, Azizah; Aszari, Efendi H.; Prameswari, Fadila A.; Ma’arif, Burhan (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Sexual arousal is an important aspect to achieve a harmonious sex life, but often disorders in normal sexual function disrupt the harmony of household relationships. One alternative natural ingredient that has the potential as an aphrodisiac agent is Lelak (Uvaria rufa) which is traditionally used by the people of East Nusa Tenggara (NTT), Indonesia, to overcome sexual dysfunction in men. This study aims to evaluate the safety and effectiveness of 70% ethanol extract of Uvaria rufa roots in vivo. This study is an experimental study to test the effectiveness of 70% ethanol extract of Uvaria rufa roots in vivo. This study was conducted with an initial stage, namely 70% ethanol extract of Uvaria rufa roots obtained through maceration, then the aphrodisiac activity was measured through the parameters of the number of leydig cells and the weight of the testes of male mice (Mus musculus).The results showed that the administration of the extract with an LD50 value of 2108 μg/ml which is included in the Relatively Harmless category, while group P2 with a dose of 0.85 mg/20g BB/day was stated as the optimal dose (p<0.05 against the negative control) for aphrodisiac activity in measuring testicular weight and the number of Leydig cells. Therefore, administration of 70% ethanol extract of Uvaria rufa roots at a dose of 0.85 mg/20g BW/day is the optimal dose for aphrodisiac activity.